Exploring mental health clients' current medication knowledge, beliefs and experience with healthcare providers in the community in South Australia. (23rd September 2022) - Bui, Tien Ngoc Thi; Hotham, Elizabeth; Loughhead, Mark; McMillan, Sara S.; Procter, Nicholas; Poole, Kessie; Suppiah, Vijayaprakash
Abstract: In Australia, mental illness has been recognised as a National Health Priority area, with the coronavirus pandemic adding a layer of urgency to the need to address the multiple health problems faced by clients with mental illnesses. Whilst much has been done in efforts to support these clients, little is known about their medication knowledge and experience with health professionals. The aim of the study was to explore the knowledge and beliefs of clients on the use of psychotropic medications and study their experiences with healthcare providers. Adult participants at a not‐for‐profit community‐managed specialist mental health service provider in Adelaide, South Australia were recruited. Four focus group sessions were conducted between February 2020 and March 2021. All sessions were co‐facilitated by a peer practitioner with lived experience. Sessions were audio recorded and transcribed verbatim. Participants ( n = 27) reported that provision of medication education was inadequate and, in some cases, non‐existent. There was an apparent lack of support for monitoring and managing common side effects, such as weight gain. Participants described not being involved in any decision‐making processes and that establishing and maintaining a therapeutic relationship with their healthcare providers was challenging. Perceived stigma remains a barrier in accessing healthcare. Despite participants regularly interacting with a range of healthcare providers, findings highlight key gaps in care, particularly medication education and establishing a therapeutic relationship with their healthcare providers. Future mental health reforms should consider the provision of additional medication education in community settings, such as at not‐for‐profit organisations. Moreover, healthcare providers should take a proactive approach in establishing therapeutic relationships.